Ideal Clinic Realisation and Maintenance programme implementation in rural KwaZulu-Natal - Donald T. Mhlungu; Geertien C. Boersema; Mokholelana M. Ramukumba (AOSIS, 2024)
Background: The delivery of quality primary healthcare (PHC) services is vital for enhancing the health status of rural communities, yet persistent barriers exist in resource-constrained rural settings. Aim: The study explored perspectives on the barriers to and facilitators of implementing the Ideal Clinic Realisation and Maintenance (ICRM) programme as a quality assurance initiative in a rural KwaZulu-Natal subdistrict. Setting: Professional nurses and healthcare managers from seven PHC clinics in a rural subdistrict of KwaZulu-Natal and supervising managers from a district hospital participated in this study. Methods: Telephonic semi-structured interviews were conducted using a qualitative case study approach with the purposively selected sample. Data were inductively and thematically analysed. Results: Themes included ICRM programme organisation, barriers and facilitators for implementing the ICRM programme. Barriers in rural PHC settings included overburdened clinics, suboptimal infrastructure, staff burnout, poor communication and non-adherence to clinical guidelines. Despite obstacles, programme implementation was facilitated through stakeholder support and teamwork. Participants emphasised the need for infrastructure upgrades, more human and physical resources, and maintenance of stakeholder support. Conclusion: If challenges are mitigated and supportive factors are leveraged, the potential for successful programme implementation and improved healthcare delivery can benefit both healthcare providers and recipients. Contribution: Through providing insight into the perspectives of both implementers and supervisors, the study informs stakeholders and policymakers about difficulties encountered and potential improvements to be made in the implementation of the ICRM programme in rural PHC.